Characterization of third molars subjected to surgical extraction at the College of Dentistry University of Antioquia between 1991 and 2001 - Rodríguez-Aguirre, Gemma Cecilia; Martínez-Herrera, Eliana; Duque-Serna, Francisco Levi; Londoño-Puerta, Lina María (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Purpose: To characterize the third molars extraction procedures performed at the operating room of the collage of Dentistry University of Antioquia, according to anatomical variables and radiographic analysis. Materials and methods: a descriptive retrospective observational study was carried out of 2120 extraction performed on 1072 patients attended between 1991 and 2001. Clinical records of patients with upper and lower third molars to whom surgery was performed with local anesthesia, high speed hand piece, and panoramic and periapical radiographic analysis were included. Results: According to the longitudinal axis of the third molar, 43.9% were vertical; according to the position of the molar with respect to the occlusal plane 41.6% of the third molars were found to be in position C; the periodontal compromise was of good prognosis in 61.5% of the cases, and on the lower third molars the most frequent classification of erupting space was type II (79.3%). The risk of impactation in the maxillary sinus was present in 34.2% of the cases. Intraoperative complications were rare. Conclusions: mesio angulated lower third molars below occlusal plane and without erupting space present the most complications, and even though they were performed by undergraduate dental students, these percentages are below the percentages reported wordwide.